2016
DOI: 10.1111/ijd.13219
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of telecytology in tertiary teledermatological consultation: a retrospective analysis of 75 cases

Abstract: This study revealed that the cytological images should be used in tertiary teledermatological evaluation. Further studies should therefore be carried out to investigate the diagnostic value of different telecytological methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Nevertheless, in most clinics, this simple test is either not performed or is only used to diagnose a few diseases, mainly due to lack of experience. In a dermatology clinic where 75 patients for whom no diagnosis could be established via face-to-face clinical examinations and cytological evaluations, telemedicine was used to overcome this issue 34 . Although this is a reasonable solution, the necessary expertise is still scarce, scheduling is necessary, and one can only examine a limited number of images during a session.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in most clinics, this simple test is either not performed or is only used to diagnose a few diseases, mainly due to lack of experience. In a dermatology clinic where 75 patients for whom no diagnosis could be established via face-to-face clinical examinations and cytological evaluations, telemedicine was used to overcome this issue 34 . Although this is a reasonable solution, the necessary expertise is still scarce, scheduling is necessary, and one can only examine a limited number of images during a session.…”
Section: Discussionmentioning
confidence: 99%
“…In a dermatology clinic where 75 patients for whom no diagnosis could be established via face-to-face clinical examinations and cytological evaluations, telemedicine was used to overcome this issue. 34 Although this is a reasonable solution, the necessary expertise is still scarce, scheduling is necessary, and one can only examine a limited number of images during a session. In this work we demonstrated that TzanckNet can identify six cell types in Tzanck smear findings.…”
Section: Discussionmentioning
confidence: 99%